The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1203475416651605
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-17 in the Pathogenesis of Psoriasis and Update on IL-17 Inhibitors for the Treatment of Plaque Psoriasis

Abstract: The IL-23/Th17 signaling pathway (including IL-17) plays a central role in the pathogenesis of psoriasis. Biologic agents that block IL-17 (secukinumab and ixekizumab) or its receptor (brodalumab) are effective and safe for the treatment of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 60 publications
(159 reference statements)
0
30
0
3
Order By: Relevance
“…IL-17 increases the expression, by keratinocytes, of chemokines involved in recruiting myeloid dendritic cells, Th17 cells, and neutrophils in the site of the lesion [1][2][3][4]. Based on these findings, several new biologics agents for the treatment of plaque psoriasis (PsO), which target IL-17, have been developed [5][6][7][8]. These new drugs include secukinumab, a fully human immunoglobulin G1 kappa (IgG1k) antibody, and ixekizumab, a humanized IgG4 monoclonal antibody, both of which selectively bind the IL-17A cytokine, as well as brodalumab, a human monoclonal antibody that blocks the IL-17 receptor, inhibiting the activity of all types of IL-17 [9].…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 increases the expression, by keratinocytes, of chemokines involved in recruiting myeloid dendritic cells, Th17 cells, and neutrophils in the site of the lesion [1][2][3][4]. Based on these findings, several new biologics agents for the treatment of plaque psoriasis (PsO), which target IL-17, have been developed [5][6][7][8]. These new drugs include secukinumab, a fully human immunoglobulin G1 kappa (IgG1k) antibody, and ixekizumab, a humanized IgG4 monoclonal antibody, both of which selectively bind the IL-17A cytokine, as well as brodalumab, a human monoclonal antibody that blocks the IL-17 receptor, inhibiting the activity of all types of IL-17 [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to recent developments in the understanding of the pathogenesis of this disease, the treatment paradigm has now shifted toward targeting specific inflammatory pathways. Biologic agents that specifically block the IL-17 pathway have shown promising results with regard to efficacy and safety 4,5…”
Section: Introductionmentioning
confidence: 99%
“…Both phase 2 and 3 trials showed the efficacy of brodalumab in the treatment of moderate-to-severe psoriasis 4,5. As a result, the US FDA approved brodalumab, for subcutaneous (SC) use, for the treatment of moderate-to-severe plaque psoriasis on February 16, 2017 6.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it was not surprising that Candida species infections were observed more frequently with secukinumab and ixekizumab than with etanercept or placebo. 6 Apart from 3 severe mucocutaneous cases reported in the UNCOVER-2 trial (1 affecting the external ear during the induction period and 2 affecting the oral mucosa between 12 and 60 weeks of treatment), all cases reported were mild to moderate. 12 No systemic Candida species infection has been reported with the anti-IL-17 mAbs.…”
Section: Psoriasismentioning
confidence: 89%
“…Two of the anti-IL-17 mAbs have obtained FDA approval for plaque psoriasis: secukinumab (Cosentyx; Novartis Pharmaceuticals Corp, Basel, Switzerland) in 2015 and ixekizumab (Taltz; Eli Lilly and Co, Indianapolis, Ind) in 2016. [6][7][8] Head-to-head clinical studies evaluating the efficacy of anti-IL-17A versus anti-TNF-a (ixekizumab vs etanercept) or anti-p40 IL-12/23 (secukinumab vs ustekinumab) showed a higher efficacy of the anti-IL-17A drugs based on Psoriasis Area Severity Index (PASI) 75, PASI-90, and PASI-100 scores (ie, 75% or greater, 90% or greater, and 100% reduction in PASI scores from baseline). [9][10][11][12] PASI is a widely used tool to assess the severity of psoriasis, providing a score in the range of 0 (no disease) to 72 (maximal disease), taking into account body surface area, as well as erythema, induration, and scaling of the plaques.…”
Section: Psoriasismentioning
confidence: 99%